Effects of Garlic and Green Tea as Alternative Feed Additives in Broiler Diet - Rashid, Md. Harun Or; Das, Shubash Chandra; Hossain, Md. Mortuza; Hossain, Md. Elias (Journal of the Bangladesh Agricultural University, 2024)
The objective of this study was to evaluate the use of garlic and green tea as alternative for safe broiler production. The experiment was done for a period of 35 days with 300 day-old Cobb-500 straight run broiler chicks. Birds were divided into five dietary treatment groups with four replications and each having 15 birds per replication. Treatments consisted as corn-soybean meal based basal diet and basal diet supplemented with 0% feed additives, 0.20% antibiotic, 0.25% garlic powder, 0.25% green tea powder and combination of garlic and green tea powder (0.125% garlic powder and 0.125% green tea powder). Body weight, feed intake of the bird were recorded every week, whereas dressing parameters, meat and bone development, serum biochemical parameters and hematological parameter were measured at the end of the experiment. Body weight, body weight gain increased (P<0.05) in the garlic and antibiotic groups compared to the control group. Higher (P<0.05) feed intake was observed in garlic group compared with the green tea, combined and control group. Improved (P<0.05) feed conversion ratio was found in garlic and green tea group alone or in a combination as well as antibiotic group compared to the control group. Abdominal fat, serum cholesterol and serum LDL were lower (P<0.05) and serum HDL was higher (P<0.05) in the supplemented groups compared to the control and antibiotic groups. Serum triglyceride was significantly (P<0.05) lower in the antibiotic, garlic, green tea and combined groups compared to the control group. Combined group showed lower (P<0.05) serum GPT and creatinine value compared to the control group; whereas lower serum GOT value was found in the antibiotic group. The results indicated that there was no significant difference (P>0.05) in hematological parameters (RBC, Hb and PCV) among the treatment groups. Taken together, addition of garlic and green tea to broiler diet had positive effect on growth performances, lipid profile and serum biochemical parameters. There was no negative effect on meat yield, bone development, carcass parameters, hematological parameters, serum GOT, GPT and creatinine value. It may be suggested that the garlic and green tea could be potential feed additives for the production of antibiotic free safe broiler. J Bangladesh Agril Univ 18(4): 1013–1020, 2020 https://doi.org/10.5455/JBAU.2939